New species of the genus Microtendipes Kieffer, 1915 (Diptera, Chironomidae) from Buryatia (Russia) - Orel, Oksana V.; Bazova, Natalia V. (Zootaxa, 2018)
Microtendipes langtoni Orel sp.n. from the Gusinoye Lake (Buryatia) is described and figured based on the morphology of the imago males, pupae and larvae.